Penerapan Microsoft Excel dalam meningkatkan pengelolaan dan analisis data nilai siswa di Sanggar Wicara - Isnurani, Isnurani; Rusdiana, Yulianti (Penamas: Journal of Community Service, 2025)
This community service activity was conducted to improve the management and analysis of student grade data at Sanggar Wicara through Microsoft Excel. Training was provided to teachers to integrate technology into the assessment process to make it more effective, efficient, and accurate. The evaluation of the training results showed high enthusiasm from the participants and uniformity in grading among teachers, which reduced score variation. Additionally, teachers utilized the provided assessment templates to enhance their work productivity. A positive response from more than 75% of the participants confirmed the success of this activity in supporting the improvement of learning quality. The findings demonstrated that the application of Microsoft Excel facilitated data processing and increased the consistency and quality of educational evaluation. These results are expected to reference similar technology implementation in other elementary schools.